Regulation and investment incentives in electricity distribution: An empirical assessment - Astrid Cullmann; Maria Nieswand (Deutsches Institut für Wirtschaftsforschung (DIW), 2015)
We analyze the effects of an incentive based regulatory scheme with revenue caps on the investment behaviors and decisions of 109 electricity distribution companies operating in Germany in 2006-2012. We hypothesize that Germany's implementation of incentive regulation in 2009 has a negative impact on total investment, and that firms increase their investments in the base year. We build a model that controls for both firm-specific heterogeneity and ownership structure and test it with the German data. The results show that investments increase after incentive regulation, and that the institutional constraints used to determine the revenue caps influence the distribution companies' investment decisions. We also note that the investments increase in the base year when the rate base is determined for the following regulatory period. We conclude that a comprehensive assessment of Germany's electricity distribution companies' investment decisions and behaviors should account for firm specific heterogeneity. It should further include all institutional aspects of incentive regulation to design incentives that will foster investments in the region's energy networks.
Keywords: L94; L51; L98; 330; Incentive Regulation; Electricity Distribution; Investments; Germany